Assessıng global governance polıcy of Turkey as a rısıng power: motıvatıons, strategıes, ınstruments - Aydın, Şükrü (My University, 2017)
Bu çalışmanın amacı özellikle motivasyonlar, stratejiler ve araçlara odaklanarak Türkiye’nin son yıllarda küresel yönetişim algılamasındaki değişimin incelenmesidir.

This work aims to understand the shifts in Turkey’s understanding of global governance in recent years with a particular focus on its motivations, strategies, and instruments.
Keywords: Dış politika; Emerging Power; Global Governance; Küresel yönetim; Küresel Yönetişim; Middle-range Power; Orta-ölçekli Güç; Rising Power; Turkish Foreign Policy; Türk Dış Politikası Turkey; Türkiye; Uluslararası ilişkiler; Yükselen Güç